Bioenergy Development : Issues and Impacts for Poverty and Natural Resource Management - Cushion, Elizabeth; Dieterle, Gerhard; Whiteman, Adrian (World Bank, Washington, DC, 2012)
The last five to ten years have seen a strong resurgence of interest in bioenergy along with the gradual development of more modern and efficient bioenergy production systems. This has been driven by several factors including instability in oil producing regions, financial market shift of investments in 2007-2008 to commodities and oil, extreme weather events, and surging energy demand from developing countries. Bioenergy developments present both opportunities and challenges for socioeconomic development and the environment and have a number of potential impacts on forests and the rural poor who depend on forests for their livelihoods. In developing countries, the impact of bioenergy on poverty alleviation will depend on the opportunities that are presented for agricultural development, including income and employment generation and the potential to increase poor peoples' access to improved types of bioenergy. There are significant concerns surrounding the efficiency of different bioenergy options to combat climate change, the impact on agriculture, food security and sustainable forest management and the social impacts of bioenergy development, particularly related to land use changes, land tenure, and land rights. Food insecurity may result if staple crops are used for energy production or land conflicts and if production displaces local communities or restricts access to land. The environmental impacts of these developments are uncertain and will vary considerably from case to case. The development of bioenergy is likely to have significant impacts on the forest sector directly, through the use of wood for energy production, and indirectly, as a result of land use changes. It is expected that energy production from solid biomass will have both direct and indirect impacts on the sector, whereas liquid biofuels will mainly have indirect effects.